THE INCIDENCE OF TETANUS IN ISFAHAN - S; Sehat; M. Mirallai K. Hazeghi (Tehran University of Medical Sciences, 1976)
The incidence of tetanus among wounded patients in greater Isfahan in 5 years with their mortality was discussed, careful review of the literature. With consideration of commendations of the committee on trauma of the American College of Surgeons, the German Association for Surgery and the Swedish College .of Surgeons about type of prophylactic measurement discussed and finally the basic trends are emphasized.